A Graph-Based Method for IFC Data Merging - Qin Zhao; Yuchao Li; Xinhong Hei; Mingsong Yang (Advances in Civil Engineering)
Collaborative work in the construction industry has always been one of the problems solved by BIM (Building Information Modeling) technology. The integration of IFC (Industry Foundation Classes) data as a general building information standard is one of the indispensable functions in collaborative work. The most practical approach of merging IFC data depends on GUID (Global Universal Identifier) comparison at present. However, GUID is not stable in current applications and often changes when exported. The intact representation of relationships between IFC entities is an essential prerequisite for proper association of IFC entities in IFC mergence. This paper proposes a graph-based method for IFC data merging. The IFC data are represented as a graphical data structure, which completely preserves the relationship between IFC entities. IFC mergence is accomplished by associating other data with an isomorphic graph that is obtained by mining the IFC graph. The feasibility of the method is proven by a program, and the method can ignore the impacts of GUID and other factors.